Potensi Pengembangan Wisata Berbasis Masyarakat Di Desa Banyuanyar, Boyolali - Hafni Khairunnisa; Trias Shofi Nur’aini (Samarinda State Polytechnic, 2020)
This study aims to find out how potentially Banyuanyar Village to developed into tourism village. Tourism village is form of implementation community based tourism. A purpose from community based tourism is to encouraged local community so they can be more prosperous. A village can be developed as well to be tourism village if fullfill several criteria tourism development. They are “potential product or potential attraction in destination”, “local community”, “potential of local human resources”, “availability of facilities and infrastructure”, and “ability to create a tourism market”. Based from thos criteria, Banyuanyar village has enough potential to be developed as a tourism village. A strong aspect are found on the tourist attraction. Currently Banyuanyar Village has been visited by tourists but is still limited to the coffee segment. The weakness that still needs to be improved is the ability to create markets. Banyuanyar village is currently still having difficulties in making tour packages, and to determine the right market segment and the right marketing strategy.